Congenital pancreatic cyst: Preoperative diagnosis and management - Osama A. Bawazir; Ahmed H. Al-Salem; Abdullah O. Bawazir (Elsevier, 2017)
Background: Congenital pancreatic cyst is very rare in infants and children. The majority of pancreatic cysts in children are pseudocysts resulting from trauma, acute pancreatitis or infection. Patients and methods: Three children with true congenital pancreatic cyst were treated. Their medical charts were reviewed for age at presentation, sex, clinical features, diagnosis and management. Results: Three children (1 male and 2 females) with a mean age of 23 months (4 months-4 years) were treated for congenital pancreatic cyst. One of them presented with an abdominal mass while another presented with non-bile stained vomiting and abdominal distension. The third was diagnosed to have left sided Wilms tumor and during investigation was found to have congenital pancreatic cyst. CT-scan and MRI were helpful in confirming the diagnosis. All were treated surgically. One had total surgical excision while the other two had cystojejunostomy. Conclusions: Congenital pancreatic cyst is very rare in the pediatric age group and should be considered in the differential diagnosis of cystic lesions of the pancreas in infants and children. Preoperative diagnosis is important to plan surgical intervention. Complete surgical excision is the treatment of choice but if this is not feasible a form of internal drainage, a cystoduodenostomy or a Roux-in-Y cystojejunostomy should be done.